Characterization of visna virus mRNA. - Filippi, P (1979)
Visna virus is a retrovirus responsible for a classical slow infection of the central nervous system of sheep. In the present work we focused our attention on the viral mRNA's. We found that, during the acute infection in vitro, (i) viral mRNA's amount to only 0.1% of the total cytoplasmic RNA, (ii) 20% of the total cytoplasmic viral RNA is found in polyribosomes, and (iii) three viral mRNA's can be identified by sucrose gradient sedimentation or polyacrylamide gel electrophoresis. Their sedimentation coefficients are 36S, 27S, and 21S.